Evaluation of antioxidant capacity and preliminary phytochemical screening of crude extracts from local capsicum frutescens fruits. - Padernal, Michael Patrick M.
Extracts of fresh, mature fruits of Capsicum frutescens were studied for their antioxidant activities. Using DPPH free radical scavenging assay, the methanol, dichloromethane, and ethyl acetate extracts showed significant antioxidant activity. The ethyl acetate extract exhibited the highest activity at 94.44+- 5.56 percent, comparable to that of the positive control (ascorbic acid), and significantly higher than the other extracts. The extracts that showed antioxidant activity were subjected to phytochemical screening to ascertain the presence of secondary plant metabolites. Alkaloids, flavonoids, saponins, tannins and terpenoids were found to be present in the extracts with antioxidant activity. The results of the phytochemical screening were further corroborated by confirmatory tests using thin-layer chromatography (TLC). The results for both the successive evaluation of the DPPH radical scavenging assay and phytochemical screening of the extracts from capsicum frutescens, notably the ethyl acetate fraction, suggest the plant is a potential source of medicinally important metabolites, particularly those with antioxidant activities.